STUDI ab-initio MEKANISME PEMBENTUKAN TRANSISI REAKSI OKSIDASI CO OLEH NO2 DI UDARA - Beri, Deski (Sainstek : Jurnal Sains dan Teknologi, 2012)
The transition state formation?s mechanism of CO oxidation reaction by molecule of NO2 has been done using ab-initio computation by Density Functional Theory (DFT). Geometry optimation was done by B3LYP and 6-31G* basis set using HyperGauss and HyperDFT computer software. The result is we hypothese that there was three transition state takes place, therewere trans-Transition State (KTt), cis-Transition State (KTc) and cyclic-Transition State (KTs). All of three was gradually takes place in a very short time intervals. Keywords: density functional theory (DFT), geometry optimation, intermediate, transition state